A Case Report of Central Nervous System Graft-Versus-Host Disease and Literature Review - Li, Mingming; Zhang, Yue; Guan, Yujia; Zhang, Zunwei; Dong, Hanbing; Zhao, Yang; Deng, Hui (Frontiers in Neurology, 2021)
As an adverse immune phenomenon, graft-versus-host disease often occurs after allogeneic hematopoietic stem cell transplantation. The incidence of acute and chronic graft-versus-host disease is about 40–60% and the mortality rate can reach 15%, which is a potentially fatal disease. There are rare GvHD cases involving the central nervous system. We reported a rare case of diffuse white matter changes after haploid bone marrow transplantation, summarizing its clinical manifestations and diagnosis and treatment in conjunction with the literature.